2009
DOI: 10.1242/jeb.033282
|View full text |Cite
|
Sign up to set email alerts
|

The effects of water temperature on the energetic costs of juvenile and adult California sea lions (Zalophus californianus): the importance of skeletal muscle thermogenesis for thermal balance

Abstract: SUMMARY, increased as water temperature approached 12°C, and suggested a potential thermal limitation in the wild. To determine whether muscle thermogenesis during activity could mitigate this limitation, we measured the active metabolic rate of juveniles swimming at water temperature (T water )5, 12 and 20°C. No significant difference (F0.377, P0.583) in swimming metabolic rate was found among water temperatures, suggesting that thermal disadvantages due to small body size in juvenile sea lions may be circ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 43 publications
1
24
0
Order By: Relevance
“…Similar results have been observed for sea otters (Enhydra lutris) which have a resting metabolic rate 2-3 times higher than allometric prediction for a terrestrial mammal of similar size (Miller, 1974;Costa, 1982;Davis et al, 1988;Williams et al, 1988). Although the thermal neutral zone has not been determined for southern sea lions, the lower critical temperature (T LC ) for adult California sea lions in water is 6.4°C (Liwanag et al, 2009), which is much lower than the mean air and water temperatures during the experimental phases of our study and the winter water temperature found in La Plata River estuary (10-12°C; Guerrero et al, 1997). Therefore, our animals were considered within their thermal neutral zone even though they had a _ V O 2 air rest higher than predicted for terrestrial mammals of similar size.…”
Section: Rest Airsupporting
confidence: 72%
See 2 more Smart Citations
“…Similar results have been observed for sea otters (Enhydra lutris) which have a resting metabolic rate 2-3 times higher than allometric prediction for a terrestrial mammal of similar size (Miller, 1974;Costa, 1982;Davis et al, 1988;Williams et al, 1988). Although the thermal neutral zone has not been determined for southern sea lions, the lower critical temperature (T LC ) for adult California sea lions in water is 6.4°C (Liwanag et al, 2009), which is much lower than the mean air and water temperatures during the experimental phases of our study and the winter water temperature found in La Plata River estuary (10-12°C; Guerrero et al, 1997). Therefore, our animals were considered within their thermal neutral zone even though they had a _ V O 2 air rest higher than predicted for terrestrial mammals of similar size.…”
Section: Rest Airsupporting
confidence: 72%
“…The average air temperature inside the box was maintained at 22.3±2.8°C (range 15-25°C) by adjusting the air flow. This temperature was within the thermal neutral zone described for California sea lions (Zalophus californianus, Lesson 1828; Costa and Williams, 1999;Hurley and Costa, 2001;Liwanag et al, 2009). We calculated the mean _ V O 2 rest air for all the animals together and for only the three adult females, even though the values were very similar.…”
Section: Metabolic Rate While Resting In Airmentioning
confidence: 93%
See 1 more Smart Citation
“…GSL increased their FMR (CO 2 production) when spent greater % time at sea, possibly due to the increased costs of thermoregulation. Although the lower critical temperature for California sea lions has been determined to be 6.4°C, measurements were taken for a period of only 30-120 min (Liwanag et al, 2009), while GSL spent from 20 to 84 h at sea on a single foraging trip. Furthermore some females in this study dived continuously to the bottom encountering average temperatures of 6.8°C (measured by temperature sensor on TDR tag).…”
Section: Field Metabolic Ratementioning
confidence: 99%
“…Boyd et al 1995, Boyd 1997, Horning & Trillmich 1997, Thompson & Fedak 2001, Costa et al 2004) of dive bouts. On the other hand, studies directly addressing transit swimming are less numerous (Ponganis et al 1990, Stelle et al 2000, Chilvers et al 2005, Insley et al 2008, with many confined by experimental logistics to surface swimming only (Butler et al 1992, Williams 1999, Rosen & Trites 2002, Liwanag et al 2009). …”
Section: Introductionmentioning
confidence: 99%